(untitled) (Academicia Globe: Inderscience Research, 2023)
Modern ststae of invasive prussian carp (Carassius gibelio) was studied in Tudakul reservoir (lower stream of Zarafshen River) in 2020-2022. Fins rays formula was D II (III) 16-18, A II 5-6; 26 - 28 scales in lateral line and 38 – 46 gil rakers were determined. Plastic indexes according to tradinional for cyprinids so as indexes of «truss protocol» are given. The ages of the samples ranged between 1 to 5 years, the total length 144.3 – 452.7 mm, the standard lengths 113.3 – 383.0 mm and total weights 99.0 – 703.0 g. The relationship between the total length (TL) and weight (W) was described by W = 0,0192*TL2,957 (r = 0,95). The mean back calculated standard length was 10.7 cm at age I; 18.1 cm, II; 24.4 cm, III;26.1 cm, IV.